2018
DOI: 10.1002/mame.201800213
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Preparing Mechanically Strong Hyaluronic Acid–Silica Nanohybrid Hydrogels via In Situ Sol–Gel Process

Abstract: A hybridization method to prepare a hyaluronic acid (HA)‐based nanohybrid hydrogel is proposed that introduces an additional inorganic silica network via an in situ sol–gel process. HA hydrogels have been extensively studied because of their excellent biocompatibility and biological functions; however, their poor mechanical strength hinders their use in tissue engineering applications. In the present work, the sol–gel technique is employed to achieve the formation of a structurally organized silica network in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Hydrogels have attracted growing attention in various fields, including tissue engineering, cell delivery, and biosensing. However, the low mechanical property brings obstacles in their huge applications. Many efforts are made to achieve high-performance hydrogels by building double-network (DN) structures, , constructing hierarchical structures and composite structures. The composite hydrogels are fabricated by blending rigid inorganic materials in the soft polymer matrix to get enhanced strength and toughness. However, the enhancement in elastic modulus of a hydrogel is rather limited. , It is shown that the interaction of inorganic fillers with polymers is essential for reinforcing composite hydrogels. At a sufficiently high filler content, the hydrogel can be rather robust, which is related to percolation. However, toughness is usually increased, while the Young’s modulus is compromised by the percolation structure. , …”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels have attracted growing attention in various fields, including tissue engineering, cell delivery, and biosensing. However, the low mechanical property brings obstacles in their huge applications. Many efforts are made to achieve high-performance hydrogels by building double-network (DN) structures, , constructing hierarchical structures and composite structures. The composite hydrogels are fabricated by blending rigid inorganic materials in the soft polymer matrix to get enhanced strength and toughness. However, the enhancement in elastic modulus of a hydrogel is rather limited. , It is shown that the interaction of inorganic fillers with polymers is essential for reinforcing composite hydrogels. At a sufficiently high filler content, the hydrogel can be rather robust, which is related to percolation. However, toughness is usually increased, while the Young’s modulus is compromised by the percolation structure. , …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the silanol groups and HYH were able to form hydrogen bonds, thereby further enhancing the mechanical properties. Cells were highly viable on these gels [106]. New gelling and crosslinking strategies have emerged as convenient and rapid methods for incorporating advanced functionality into HYH-silica gels [107,108].…”
Section: Silicamentioning
confidence: 99%
“…Composites of HYH and silica (SiO 2 ) have been developed ( Supplementary Materials, Table S1 ) as hydrogels or films for many applications, such as drug delivery and tissue engineering. One promising manufacturing strategy [ 106 ] involved taking advantage of sol–gel synthesis and freeze-drying to produce the interconnected microporous structure of the HYH-SiO 2 gels. Increasing the silica content in the gel formed more dense gels.…”
Section: Hyh–bioceramic and Hyh–bioglass Compositesmentioning
confidence: 99%
See 2 more Smart Citations